Zmiany na rynku pracy miasta Bydgoszczy w latach 2000-2014 = Changes in the labour market of the city of Bydgoszcz in the years 2000-2014 - Gabriela Barwińska-Szczutkowska; Kazimierz Harłoziński; Jacek Szczutkowski (Kazimierz Wielki University, 2015)
Barwińska-Szczutkowska Gabriela, Harłoziński Kazimierz, Szczutkowski Jacek. Zmiany na rynku pracy miasta Bydgoszczy w latach 2000-2014 = Changes in the labour market of the city of Bydgoszcz in the years 2000-2014. Journal of Education, Health and Sport. 2015;5(12):744-766. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49756 http://ojs.ukw.edu.pl/index.php/johs/article/view/3453     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.     Zmiany na rynku pracy miasta Bydgoszczy w latach 2000-2014 Changes in the labour market of the city of Bydgoszcz in the years 2000-2014     Gabriela Barwińska-Szczutkowska, Kazimierz Harłoziński, Jacek Szczutkowski   Instytut Geografii, Wydział Kultury Fizycznej, Zdrowia i Turystyki, UKW Bydgoszcz     Streszczenie. W artykule przedstawiono problematykę zmian na rynku pracy w mieście Bydgoszczy w okresie 2000-2014 na tle województwa kujawsko-pomorskiego. Szczególną uwagę zwrócono na rangę miasta, jego rozwój funkcjonalny oraz bazę przemysłową.   Słowa klucze: rynek pracy, zatrudnienie, bezrobocie, Bydgoszcz.   Abstract: The article gives the issue of labour market developments in the city of Bydgoszcz in the period 2000-2014 on the background of kujawsko-pomorskie voivodeship. Special attention has been paid to the rank of city, its functional development and industrial base.   Key words: labour market, employment, unemployment, Bydgoszcz.